Transmission investigation of Mycoplasma synoviae in Chinese indigenous chickens - Yin, Liping; Luo, Yan; Li, Changming; Yin, Hanjie; Zhou, Qiang; Cui, Shutao; Xu, Moru; Zhang, Haitao; Qin, Aijian; Wang, Li (Frontiers in Veterinary Science, 2025)
Mycoplasma synoviae (MS) induces avian synovitis, presenting with tendon inflammation, and respiratory distress, ultimately compromising poultry health and farm productivity. To investigate the epidemiological characteristics of MS in Chinese indigenous chickens, a comprehensive study was conducted on chicken flocks from three breeder farms in Jiangsu, China. A total of 113 batches of chicken flocks were screened using real-time polymerase chain reaction (qPCR). Among 3,284 choanal cleft swab samples collected from chickens aged 2 to over 25 weeks, 1,695 tested positive for MS. Notably, the MS-positive rate increased significantly in chickens aged 8 to 25 weeks. Interestingly, none of the chicken embryo samples (0/322) and only two one-day-old chickens (2/927) tested positive for MS infection. In contrast, Mycoplasma gallisepticum (MG) infection was more prevalent, particularly in unhatched embryos (158/294), primarily due to air sac contamination. All offspring from MS-positive parent flocks aged 27 to 38 weeks tested negative for MS. To further explore the influence of the breeding environment, chickens from the same batch were raised either in breeder farms or isolators for 17 weeks. Chickens housed in breeder farms exhibited MS nucleic acid and antibody positivity from 9 to 17 weeks, whereas those raised in isolators remained MS-free throughout the study. These findings indicate that vertical transmission of MS in Chinese indigenous chickens is rare, with horizontal transmission being the predominant mode of spread.